Offensive strategies in the European Football Championship 2012 - Sgrò, F.; Aiello, F.; Casella, A.; Lipoma, M. (Perceptual and Motor Skills, 2016)
The aim of this study was to identify the independent and interactive effects of possession strategy, pitch location, and game period on the offensive actions performed by the winning teams in the 2012 European Football Championship. The non-clinical magnitude-based inferences method was used to interpret the true effect of the performance indicators on the response variable. The offensive team possessions were grouped into winning (n = 2035) and losing (n = 2071). The winning teams performed offensive processes mainly using the possession play strategy (OR: 0.75, very likely negative effect of the direct play). When the analysis included the pitch location, negative interaction effect was found for the direct play, which ended up in the central path (OR: 0.70, very likely negative effect). On the contrary, the direct play in the second half of the match seemed to produce an effect on the probability of the winning teams performing offensive processes (OR: 1.59, most likely positive effect). The results of multivariate analyses showed that the offensive team possession profiles required a careful investigation because the possession strategy changed under the conjoint effect of pitch location and game period. ABSTRACT FROM AUTHOR